STUDENTS' ATTITUDE TOWARDS TALKING CIRCLE AS AN EFLSPEAKING ACTIVITY IN SENIOR HIGH SCHOOL - Igel Prameswari, - (2023)
There are only a few opportunities for students to talk using the meaningful use of a language in EFL classrooms. A talking circle is an activity in the form of a circle that can provide a rich opportunity for students to extend their EFL speaking ability. It creates opportunities for learners to engage in meaningful communication and to practice social knowledge with others. Students' attitudes toward this activity must be considered carefully, because a positive attitude leads to the success of an activity. This paper is aimed to investigate high school students' attitudes towards talking circles as a speaking activity in an EFL classroom, as well as the factors that cause such attitudes. This case study adopts observation, questionnaire, and interview in collecting the data from thirteen students of the same class in a public high school in Bandung. The finding shows that students have positive attitudes towards this activity. The factors that cause these positive attitudes are power and influence of a language, pride of a language, and experience in learning a language. The results of this study are beneficial for EFL teachers, as they can implement this activity in the classroom. Researchers for future studies should pay attention to time management. It is best to conduct the research after students have finished final exams.